Correlative scanning electron and confocal microscopy imaging of labeled cells coated by indium‐tin‐oxide. Issue 6 (22nd March 2015) - Rodighiero, Simona; Torre, Bruno; Sogne, Elisa; Ruffilli, Roberta; Cagnoli, Cinzia; Francolini, Maura; Di Fabrizio, Enzo; Falqui, Andrea
ABSTRACT: Confocal microscopy imaging of cells allows to visualize the presence of specific antigens by using fluorescent tags or fluorescent proteins, with resolution of few hundreds of nanometers, providing their localization in a large field‐of‐view and the understanding of their cellular function. Conversely, in scanning electron microscopy (SEM), the surface morphology of cells is imaged down to nanometer scale using secondary electrons. Combining both imaging techniques have brought to the correlative light and electron microscopy, contributing to investigate the existing relationships between biological surface structures and functions. Furthermore, in SEM, backscattered electrons (BSE) can image local compositional differences, like those due to nanosized gold particles labeling cellular surface antigens. To perform SEM imaging of cells, they could be grown on conducting substrates, but obtaining images of limited quality. Alternatively, they could be rendered electrically conductive, coating them with a thin metal layer. However, when BSE are collected to detect gold‐labeled surface antigens, heavy metals cannot be used as coating material, as they would mask the BSE signal produced by the markers. Cell surface could be then coated with a thin layer of chromium, but this results in a loss of conductivity due to the fast chromium oxidation, if the samples come in contact with air. In order to overcome these major limitations, a thin layer of indium‐tin‐oxide was deposited by ion‐sputtering on gold‐decorated HeLa cells and neurons. Indium‐tin‐oxide was able to provide stable electrical conductivity and preservation of the BSE signal coming from the gold‐conjugated markers. Microsc. Res. Tech. 78:433–443, 2015 . © 2015 Wiley Periodicals, Inc.